2009
DOI: 10.1111/j.1365-2753.2008.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Parkinson's disease by Hoehn–Yahr stage from community‐based and clinic series [Keelung Community‐based Integrated Screening (KCIS) no. 17)]

Abstract: The present study revealed that early detection of PD through a community-based survey may reduce 51% incidence of stage III or more severe PD at diagnosis, leading to a 25% reduction in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In order to capture the effect of increased mortality risk for individuals with PD and the relationship between disease status and mortality, we used age-specific all-cause general population mortality rates from the UK [58], to which we applied relative risks within each H&Y stage to reflect increasing mortality risk with disease progression, using data from a community-based study [49]. …”
Section: Methodsmentioning
confidence: 99%
“…In order to capture the effect of increased mortality risk for individuals with PD and the relationship between disease status and mortality, we used age-specific all-cause general population mortality rates from the UK [58], to which we applied relative risks within each H&Y stage to reflect increasing mortality risk with disease progression, using data from a community-based study [49]. …”
Section: Methodsmentioning
confidence: 99%
“…Early detection and treatment of IPD may increase life expectancy . One study found that IPD cases detected early had a 51% lower incidence of Stage III or greater and 25% lower mortality . The results of the current study suggest that the active detection method identified more Stage I and II IPD cases (82.7%) than did the NHI claims records (52%, P = .003).…”
Section: Discussionmentioning
confidence: 50%
“…A previous study found that subjects in H‐Y Stage I may have the same life expectancy as the general population . Early detection and treatment of IPD may increase life expectancy .…”
Section: Discussionmentioning
confidence: 95%
“…Probability of death was calculated from the US life tables 32 with an adjustment based on the relative risk of death given the patients' age and PD severity, informed by Liou et al 38 Mortality hazard ratios based on age and Hoehn and Yahr stage are shown in the Online Supplementary Material, Table S1.…”
Section: Mortality Inputsmentioning
confidence: 99%